Performance in tax research tasks: The joint effects of knowledge and accountability. - Cloyd, C. Bryan (The Accounting Review, 1997)
Abstract This study investigates the separate and joint effects of prior knowledge and accountability on performance in the information search phase of a tax research task. An experiment is reported in which 63 tax professionals performed a computer-based tax research task. The results indicate that increases in effort duration, which are partly attributable to the accountability manipulation, improved search effectiveness regardless of the level of prior knowledge. In addition, after controlling for the effect of effort duration, accountability had an incremental positive effect on performance among the more knowledgeable professionals. These results suggest that effort can substitute for knowledge in performing information search tasks, but this substitution does not appear to be complete. The results also support the hypothesis that the effect of accountability on performance depends upon the level of knowledge, which suggests that certain aspects of effort and knowledge act as complements in improving performance.